Manfaat Fisik Dan Spiritual Dari Rutinitas Shalat - Abdul Malik; Mustafiyanti Mustafiyanti (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
The aim of this research is to determine the effect of prayer on health. This research technique uses a literature review approach. A literature review is a description of literature related to a particular discussion found in scientific articles or books. The results of this research illustrate the benefits of the connection between prayer and health, where the prayer movement contains many aspects of relaxation so that it can relieve nervous tension that arises due to various pressures in a person's life, as well as reducing the anxiety that is being felt. Therefore, we as Muslims must be more active and enthusiastic in carrying out prayer solemnly, because in prayer our soul and body focus on one central point in which we believe, namely Allah. It is even explained in Q.s. Al-An'am: 79;